A kind of steam turbine circulating water scale inhibitor and dispersant and preparation method thereof
By using a scale inhibiting dispersant equipped with organic phosphoric acid compounds, water-soluble zinc salts, acrylic copolymers and corrosion inhibitors in the turbine circulation water system, the problem of poor stability of scale inhibitors in high-salt environments is solved, and better scale inhibition effect and stability are achieved.
Patent Information
- Application Number
- CN202411152127.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-21
AI Technical Summary
In the steam turbine circulating water system, due to the continuous circulation and evaporation of cooling water, the salt concentration in the water gradually increases, resulting in an increase in the interaction force between the scale inhibitor molecules, which is prone to salting out, which reduces the stability and scale inhibition effect of the scale inhibitor.
A steam turbine circulating water scale-resistant dispersant is used, and its formulation includes 6 to 13% organophosphoric acid compound, 1 to 5% water-soluble zinc salt, 10 to 15% acrylic acid copolymer, 5 to 12% corrosion inhibitor, 1.5 to 3% stabilizer. The comonomers include unsaturated carboxylic acid, olefins with sulfonic acid groups, methoxy polyethylene glycol methyl methacrylate and divinylbenzene. Through the combination of these components, the stability of the copolymer in a high-salt aqueous solution is improved.
It significantly improves the stability and scale resistance effect of scale inhibitor in a high-salt environment, reduces the occurrence of salting out phenomenon, and ensures that the scale inhibitor effectively prevents scale formation.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of water treatment, and in particular to a turbine circulating water scale inhibitor and a preparation method thereof. Background Art
[0002] The turbine circulating water system effectively reduces the heat generated during the operation of the turbine by continuously recycling cooling water, ensuring the normal operation of the equipment. However, with the continuous use and evaporation of circulating water, the mineral content in the water gradually increases, especially hardness salts such as calcium and magnesium. These salts are very easy to deposit on the metal surfaces of cooling pipes, heat exchangers and turbine bodies under high temperature and high pressure conditions, forming a hard scale layer.
[0003] The harm caused by scale deposition to the circulating water system of steam turbines is multifaceted. First, the formation of scale greatly reduces the heat transfer efficiency, increases energy consumption, and increases the operating cost of equipment. Secondly, the scale is dense and has poor thermal conductivity, which can easily form local high temperatures under the scale, accelerate the corrosion of metal materials, and shorten the service life of equipment. In addition, the deposition of scale can also block pipes, affect the smoothness of water flow, and in severe cases even cause equipment failure or shutdown, causing huge losses to production.
[0004] In order to solve the above-mentioned problem of scale deposition in the circulating water system, the industry generally adopts the method of adding antiscalants, which can convert hardness salts in water into insoluble precipitates or prevent the deposition of particulate matter through adsorption. They can not only effectively prevent the formation of scale, but also inhibit the formation of scale to a certain extent, protecting production equipment.
[0005] However, in the turbine circulating water system, due to the continuous circulation and evaporation of cooling water, the salt concentration in the water gradually increases, forming an environment with high salt content. In this environment, the interaction force between scale inhibitor molecules is enhanced, and salting out is prone to occur, that is, the scale inhibitor molecules precipitate from the aqueous solution to form solid precipitation. The salting out phenomenon not only reduces the solubility of the scale inhibitor in water, but also weakens its scale inhibition and dispersion effect, making it impossible for the scale inhibitor that should have played a role to effectively prevent the formation of scale. Therefore, in high-salinity water, how to improve the stability and scale inhibition effect of scale inhibitors has become a problem that needs to be solved urgently in the current industrial water treatment field. Summary of the invention
[0006] In order to alleviate the problem that scale inhibitors have poor stability and are prone to salting out in a highly concentrated salt environment, the present application provides a turbine circulating water scale inhibitor dispersant and a preparation method thereof.
[0007] In a first aspect, the present application provides a turbine circulating water scale inhibitor dispersant, which comprises, by mass percentage:
[0008] 6-13% organic phosphoric acid compound, 1-5% water-soluble zinc salt, 10-15% acrylic copolymer, 5-12% corrosion inhibitor, 1.5-3% stabilizer, and water as the balance; in parts by mass, the comonomers of the acrylic copolymer include: 10-20 parts of unsaturated carboxylic acid, 5-15 parts of olefin having sulfonic acid group, 10-20 parts of methoxy polyethylene glycol methyl methacrylate, and 2-5 parts of divinylbenzene.
[0009] Preferably, the unsaturated carboxylic acid is one or more of acrylic acid, maleic acid, fumaric acid and itaconic acid.
[0010] Preferably, the olefin having a sulfonic acid group is 2-acrylamido-2-methylpropanesulfonic acid, sodium styrenesulfonate, sodium 3-allyloxy-2-hydroxypropanesulfonate, allyl polyethylene glycol sulfonic acid, sodium allyl alkyl succinate sulfonate or 3-allyloxy-2-hydroxypropanesulfonic acid.
[0011] In the present application, the organic phosphoric acid compound is combined with the zinc salt to quickly form a dense protective film on the metal surface of the equipment, which plays a role in preventing electrochemical corrosion. In addition, the zinc salt can react with the carbonate in the water to form zinc carbonate precipitation, thereby reducing the formation of calcium carbonate and preventing the formation of scale. The acrylic copolymer mainly complexes the hardness ions (such as calcium and magnesium ions) in the water to prevent them from forming insoluble precipitates with carbonate ions. Therefore, the purpose of this scheme is to solve the stability problem of acrylic copolymers under high salt concentrations.
[0012] To this end, the present application uses unsaturated carboxylic acids, olefins with sulfonic acid groups, methoxy polyethylene glycol methyl methacrylate, and divinylbenzene as comonomers. Among them, the olefins with sulfonic acid groups can introduce sulfonic acid groups into the copolymer, which has a strong solvation effect, helps to increase the hydrodynamic volume and viscosity-increasing effect of the polymer in aqueous solution, and improves its stability in high-salinity aqueous solution systems. Methoxy polyethylene glycol methyl methacrylate and divinylbenzene respectively play the role of enhancing the steric hindrance effect of the side groups of the copolymer molecular chain and the rigidity of the polymer, significantly increasing the stability of the copolymer in the high-salinity aqueous solution system, reducing the salting-out phenomenon, and ensuring the scale inhibition effect.
[0013] Preferably, the acrylic copolymer is prepared by reacting comonomers in the presence of an initiator.
[0014] Exemplarily, the initiator is dibenzoyl peroxide, and its usage is 1% to 2% of the mass fraction of the comonomer.
[0015] Preferably, the olefin having a sulfonic acid group is 2-acrylamido-2-methylpropanesulfonic acid and sodium styrenesulfonate in a mass ratio of 1:1-2.
[0016] For olefin monomers with sulfonic acid groups, the acrylamide group in 2-acrylamide-2-methylpropane sulfonic acid is used in combination with the sulfonic acid group to have a strong scale inhibition and steric hindrance effect, which helps to improve the scale inhibition rate of the copolymer. However, adding appropriate sodium styrene sulfonate can increase the distribution density of the sulfonic acid group in the copolymer, which helps to improve the stability of the copolymer in high-salt aqueous solutions. Therefore, using appropriate amounts of 2-acrylamide-2-methylpropane sulfonic acid and sodium styrene sulfonate will ultimately result in more outstanding scale inhibition performance.
[0017] Preferably, the organic phosphoric acid compound is one or more of hydroxyethylene diphosphoric acid, diethylenetriamine pentamethylene phosphonate or hexamethylenediaminetetramethylene phosphonate.
[0018] Preferably, the water-soluble zinc salt is selected from one or more of zinc chloride, zinc nitrate or zinc sulfate.
[0019] Preferably, the raw material of the scale inhibitor and dispersant further includes 2-4% L-cysteine.
[0020] L-cysteine contains a variety of coordination groups such as thiol, amino, and carboxyl groups, which can quickly complex with the metal surface of the equipment to form an anti-corrosion protective film. In addition, L-cysteine can also be combined with organic phosphate compounds and zinc salts to form a more dense and stable protective film to improve corrosion resistance.
[0021] Preferably, the corrosion inhibitor is dicarboxy diphenyl disulfide and azole compounds.
[0022] Preferably, the azole compound includes one or more of carboxybenzotriazole, aminobenzothiazole, and mercaptobenzothiazole.
[0023] Azoles have nitrogen-containing azole rings that can form a protective film on the metal surface. The addition of dicarboxy diphenyl sulfide is to cooperate with azole compounds, especially aminobenzothiazole and mercaptobenzothiazole, to form a dense membrane structure through cross-linking. In addition, it has a certain antibacterial and antibacterial effect, which can inhibit the reproduction of microorganisms and prevent the probability of microorganisms secreting extracellular polymers that interact with hardness metal ions to form a scale film.
[0024] Preferably, the stabilizer comprises a nonionic surfactant and polyvinyl pyrrolidone.
[0025] The stabilizer in the present application is used to improve the storage stability of the scale inhibitor and dispersant and reduce the stratification and precipitation phenomenon in the system. Among them, polyvinyl pyrrolidone can improve the storage stability of the system through its viscosity-increasing effect.
[0026] In a second aspect, the present application provides a method for preparing a scale inhibitor and dispersant for turbine circulating water, which comprises the following operations: adding a water-soluble zinc salt, a stabilizer, and a corrosion inhibitor into water, stirring to dissolve, and then sequentially adding an organic phosphoric acid compound and an acrylic acid copolymer, stirring evenly to obtain the product.
[0027] In summary, this application has the following beneficial effects:
[0028] The present application obtains a polyacrylic acid copolymer through free radical copolymerization, which has good scale inhibition effect and can complex with hard metal ions such as calcium and magnesium in circulating water to reduce the formation of scale layer. At the same time, due to the introduction of sulfonic acid groups, long-chain methoxy polyethylene glycol methyl methacrylate and divinylbenzene with cross-linking effect and rigid benzene ring, the solvation effect, steric hindrance and rigidity of the copolymer are enhanced respectively, giving the copolymer excellent stability in high-salinity systems and ensuring its scale inhibition and anti-corrosion effect.
[0029] In addition, the corrosion inhibitors used in the present application are dicarboxyl diphenyl disulfide and azole compounds, which not only improve the corrosion resistance of the metal surface of the equipment, but also inhibit the reproduction of microorganisms, reduce the biofilm scale formed by the combination of extracellular polymers and ions, and improve the scale inhibition effect. DETAILED DESCRIPTION
[0030] Preparation Example
[0031] Preparation Example 1
[0032] Acrylic acid copolymer, the preparation method is as follows:
[0033] Add 3L of isopropanol to a reaction container, weigh 170g of maleic acid, 75g of 2-acrylamido-2-methylpropanesulfonic acid, 40g of sodium styrene sulfonate, 130g of methoxypolyethylene glycol methyl methacrylate, and 40g of divinylbenzene and add them to the reaction container. After stirring to dissolve, fill the reaction container with nitrogen for 30 minutes to exhaust the air in the reaction container.
[0034] Weigh 6.8g of dibenzoyl peroxide and dissolve it in acetone to obtain a 20wt% initiator solution. When the temperature of the reaction system rises to 60°C, pump the initiator solution into the reaction vessel and control the pumping time to 0.5h. After the initiator solution is added, heat it to 68°C and keep it warm for 5h. After the reaction is completed, cool it to room temperature and add sodium hydroxide solution to the reaction system to make the pH value of the solution reach 7.5-8.0. Discharge the material, remove the solvent by vacuum distillation to obtain a copolymer product, wash the copolymer product with ether, and dry it in an oven to constant weight.
[0035] Preparation Example 2
[0036] Acrylic acid copolymer, the preparation method is as follows:
[0037] Add 3L of isopropanol to the reaction container, weigh 110g of maleic acid, 75g of 2-acrylamido-2-methylpropanesulfonic acid, 75g of sodium styrene sulfonate, 100g of methoxypolyethylene glycol methyl methacrylate, and 20g of divinylbenzene and add them to the reaction container. After stirring to dissolve, fill the reaction container with nitrogen for 30 minutes to exhaust the air in the reaction container.
[0038] Weigh 4.1g of dibenzoyl peroxide and dissolve it in acetone to obtain a 20wt% initiator solution. When the temperature of the reaction system rises to 50°C, pump the initiator solution into the reaction vessel and control the pumping time to 0.5h. After the initiator solution is added, heat it to 72°C and keep it warm for 5h. After the reaction is completed, cool it to room temperature and add sodium hydroxide solution to the reaction system to make the pH value of the solution reach 7.5-8.0. Discharge the material, remove the solvent by vacuum distillation to obtain a copolymer product, wash the copolymer product with ether, and dry it in an oven to constant weight.
[0039] Preparation Example 3
[0040] Acrylic acid copolymer, the preparation method is as follows:
[0041] Add 3L of isopropanol to a reaction container, weigh 200g of acrylic acid, 50g of 2-acrylamido-2-methylpropanesulfonic acid, 30g of sodium styrene sulfonate, 180g of methoxypolyethylene glycol methyl methacrylate, and 50g of divinylbenzene and add them to the reaction container. After stirring to dissolve, fill the reaction container with nitrogen for 30 minutes to exhaust the air in the reaction container.
[0042] Weigh 8.0g of dibenzoyl peroxide and dissolve it in acetone to obtain a 20wt% initiator solution. When the temperature of the reaction system rises to 50°C, pump the initiator solution into the reaction vessel and control the pumping time to 1h. After the initiator solution is added, heat it to 70°C and keep it warm for 6h. After the reaction is completed, cool it to room temperature and add sodium hydroxide solution to the reaction system to make the pH value of the solution reach 7.5-8.0. Discharge the material, remove the solvent by vacuum distillation to obtain a copolymer product, wash the copolymer product with ether, and dry it in an oven to constant weight.
[0043] Preparation Example 4
[0044] The acrylic acid copolymer is different from that of Preparation Example 1 in that sodium styrene sulfonate is replaced by an equal amount of 2-acrylamido-2-methylpropane sulfonic acid.
[0045] Preparation Example 5
[0046] The acrylic acid copolymer is different from that of Preparation Example 1 in that an equal amount of sodium styrene sulfonate is used to replace 2-acrylamido-2-methylpropane sulfonic acid.
[0047] Preparation Example 6
[0048] The acrylic acid copolymer is different from that of Preparation Example 1 in that 2-acrylamido-2-methylpropanesulfonic acid and sodium styrenesulfonate are replaced by an equal amount of maleic acid.
[0049] Preparation Example 7
[0050] The acrylic copolymer is different from that of Preparation Example 6 in that methyl methacrylate is used in place of methoxypolyethylene glycol methyl methacrylate in an equal amount.
[0051] Preparation Example 8
[0052] The acrylic copolymer is different from that of Preparation Example 7 in that divinylbenzene is replaced by an equal amount of styrene. Example
[0053] Example 1, a turbine circulating water scale inhibitor dispersant, the raw material ratio per 1kg product is:
[0054] 9.5% organic phosphoric acid compound, 3.3% water-soluble zinc salt, 13.8% acrylic acid copolymer of Preparation Example 1, 7.5% corrosion inhibitor, 2.2% stabilizer, 2.6% L-cysteine, 61.1% water. Among them, the organic phosphoric acid compound is diethylenetriamine pentamethylenephosphonate, the water-soluble zinc salt is zinc chloride, the corrosion inhibitor is 3,3'-dicarboxy diphenyl disulfide and aminobenzothiazole in a mass ratio of 1:2, and the stabilizer is Span 60 and polyvinyl pyrrolidone in a mass ratio of 1:1.2.
[0055] The preparation method is as follows: adding water-soluble zinc salt, stabilizer and corrosion inhibitor into water at 300 rpm, stirring at 900 rpm for 20 minutes, then adding organic phosphoric acid compound, L-cysteine and acrylic acid copolymer in sequence at 300 rpm, stirring at 500 rpm for 15 minutes, and obtaining turbine circulating water scale inhibitor dispersant.
[0056] Example 2, a scale inhibitor and dispersant for circulating water of a steam turbine, the raw material ratio per 1kg of the product is:
[0057] 6.0% organic phosphoric acid compound, 1.5% water-soluble zinc salt, 10.8% acrylic acid copolymer of Preparation Example 2, 12.0% corrosion inhibitor, 2.8% stabilizer, 4.0% L-cysteine, 62.9% water. Among them, the organic phosphoric acid compound is diethylenetriamine pentamethylenephosphonate, the water-soluble zinc salt is zinc chloride, the corrosion inhibitor is 3,3'-dicarboxy diphenyl disulfide and aminobenzothiazole in a mass ratio of 1:3, and the stabilizer is Tween 80 and polyvinyl pyrrolidone in a mass ratio of 1:0.8.
[0058] The preparation method is as follows: adding water-soluble zinc salt, stabilizer and corrosion inhibitor into water at 300 rpm, stirring at 900 rpm for 20 minutes, then adding organic phosphoric acid compound, L-cysteine and acrylic acid copolymer in sequence at 300 rpm, stirring at 500 rpm for 20 minutes, and preparing turbine circulating water scale inhibitor dispersant.
[0059] Example 3, a turbine circulating water scale inhibitor dispersant, the raw material ratio of each 1kg product is: 12.4% organic phosphoric acid compound, 5.0% water-soluble zinc salt, 15.0% acrylic acid copolymer of Preparation Example 3, 5.5% corrosion inhibitor, 1.5% stabilizer, 2.0% L-cysteine, 58.6% water. Among them, the organic phosphoric acid compound is hydroxyethylene diphosphoric acid, the water-soluble zinc salt is zinc chloride, the corrosion inhibitor is 3,3'-dicarboxy diphenyl disulfide and mercaptobenzothiazole in a mass ratio of 1:1.5, and the stabilizer is Tween 80 and polyvinyl pyrrolidone in a mass ratio of 1:1.5.
[0060] The preparation method is as follows: adding water-soluble zinc salt, stabilizer and corrosion inhibitor into water at 300 rpm, stirring at 1000 rpm for 20 minutes, then adding organic phosphoric acid compound, L-cysteine and acrylic acid copolymer in sequence at 300 rpm, stirring at 500 rpm for 20 minutes, and preparing turbine circulating water scale inhibitor dispersant.
[0061] Example 4, a scale inhibitor and dispersant for circulating water of a steam turbine, is different from Example 1 in that the acrylic acid copolymer of Preparation Example 4 is replaced by an equal amount of the acrylic acid copolymer of Preparation Example 1.
[0062] Example 5, a scale inhibitor and dispersant for circulating water of a steam turbine, is different from Example 1 in that the acrylic acid copolymer of Preparation Example 5 is replaced by an equal amount of the acrylic acid copolymer of Preparation Example 1.
[0063] Example 6, a scale inhibitor and dispersant for circulating water of a steam turbine, differs from Example 1 in that L-cysteine is replaced by an equal amount of an organic phosphoric acid compound.
[0064] Example 7, a scale inhibitor and dispersant for circulating water of a steam turbine, is different from Example 1 in that an equal amount of 3,3'-dicarboxy diphenyl disulfide is used to replace aminobenzothiazole.
[0065] Example 8, a scale inhibitor and dispersant for circulating water of a steam turbine, is different from Example 1 in that an equal amount of aminobenzothiazole is used to replace 3,3'-dicarboxy diphenyl disulfide.
[0066] Example 9, a scale inhibitor and dispersant for circulating water of a steam turbine, differs from Example 1 in that polyvinyl pyrrolidone is replaced by an equal amount of Span 60.
[0067] Example 10, a scale inhibitor and dispersant for circulating water of a steam turbine, differs from Example 1 in that an equal amount of polyvinyl pyrrolidone is used to replace Span 60. Comparative Example
[0068] Comparative Example 1 is a scale inhibitor and dispersant for circulating water of a steam turbine. The difference from Example 6 is that the acrylic acid copolymer of Preparation Example 6 is used to replace the acrylic acid copolymer of Preparation Example 1 in an equal amount.
[0069] Comparative Example 2 is a scale inhibitor and dispersant for circulating water of a steam turbine. The difference from Example 6 is that the acrylic acid copolymer of Preparation Example 7 is used in an equal amount to replace the acrylic acid copolymer of Preparation Example 1.
[0070] Comparative Example 3, a scale inhibitor and dispersant for circulating water of a steam turbine, is different from Example 6 in that the acrylic acid copolymer of Preparation Example 1 is replaced by an equal amount of the acrylic acid copolymer of Preparation Example 8.
[0071] Comparative Example 4: commercially available corrosion and scale inhibitor.
[0072] Performance testing
[0073] 1. Scale inhibition performance test
[0074] With reference to the provisions of GB / T16632-2008, the scale inhibition rate of the scale inhibitor dispersant in the above examples or comparative examples in a high-salinity environment has been measured. It should be noted that in order to provide a high-salinity test environment, the test solution preparation was adjusted, and the specific preparation method is as follows:
[0075] Add 250ml of water to a 500ml volumetric flask, and use a burette to add a certain volume of calcium chloride standard solution to make the amount of calcium ions 120mg and the sodium ion content 100mg (the titrant is sodium eosin indicator). Use a pipette to add 25.0mL of water treatment agent sample solution and mix well. Then add 20ml of borax buffer solution, shake well, and use a burette to slowly add a certain volume of sodium bicarbonate standard solution (stirring while adding) to make the amount of bicarbonate ions 366mg, dilute with water to the scale, and shake well.
[0076] 2. Corrosion inhibition performance test
[0077] The corrosion inhibition rate of the corrosion and scale inhibitor in the above examples or comparative examples was evaluated by testing according to the provisions of GB / T 18175-2000; the amount of the corrosion and scale inhibitor used was 50 mg / L.
[0078] 3. Storage stability test
[0079] Weigh 100 g of the scale inhibitor and dispersant in each embodiment and comparative example, fill them into sealed glass containers, place them in an oven at 50° C. for 7 days, take them out and place them at room temperature for 24 hours to observe whether stratification and precipitation occur.
[0080] Table 1. Performance test results
[0081]
[0082] It can be seen from Table 1 that, compared with the comparative example, the scale inhibitor dispersant of the embodiment of the present application has a better scale inhibition effect in a high-salinity environment. The reason may be that the sulfonic acid group, long-chain E0 group and cross-linking group introduced by the acrylic acid copolymer, the main scale inhibition component of the present application, can significantly improve the anti-salting performance of the copolymer, ensuring its stability in a high-salinity environment and its scale inhibition effect.
[0083] The embodiments of the present application are described above, but the present application is not limited to the above-mentioned specific implementation modes. The above-mentioned specific implementation modes are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A scale inhibitor and dispersant for circulating water of a steam turbine, characterized in that: In terms of mass percentage, it includes: 6-13% organic phosphoric acid compound, 1-5% water-soluble zinc salt, 10-15% acrylic acid copolymer, 5-12% corrosion inhibitor, 1.5-3% stabilizer, 2-4% L-cysteine, and water as the balance; in parts by mass, the comonomers of the acrylic acid copolymer include: 10-20 parts of unsaturated carboxylic acid, 5-15 parts of olefin having sulfonic acid group, 10-20 parts of methoxy polyethylene glycol methyl methacrylate, and 2-5 parts of divinylbenzene; The corrosion inhibitor is made of dicarboxyl diphenyl disulfide and azole compounds in a mass ratio of 1:1.5-3; the azole compounds include one or more of carboxyl benzotriazole, aminobenzothiazole, and mercaptobenzothiazole.
2. The scale inhibitor and dispersant according to claim 1, characterized in that: The unsaturated carboxylic acid is one or more of acrylic acid, maleic acid, fumaric acid and itaconic acid.
3. The scale inhibitor and dispersant according to claim 1, characterized in that: The olefin having a sulfonic acid group is 2-acrylamido-2-methylpropanesulfonic acid, sodium styrenesulfonate, sodium 3-allyloxy-2-hydroxypropanesulfonate, allyl polyethylene glycol sulfonic acid, sodium allyl alkyl succinate sulfonate or 3-allyloxy-2-hydroxypropanesulfonic acid.
4. The scale inhibitor and dispersant according to claim 1, characterized in that: The olefin having a sulfonic acid group is 2-acrylamide-2-methylpropanesulfonic acid and sodium styrenesulfonate in a mass ratio of 1:1-2.
5. The scale inhibitor and dispersant according to claim 1, characterized in that: The organic phosphoric acid compound is one or more of hydroxyethylene diphosphoric acid, diethylene triamine pentamethylene phosphonate or hexamethylene diamine tetramethylene phosphonate.
6. The scale inhibitor and dispersant according to claim 1, characterized in that: The stabilizer comprises a nonionic surfactant and polyvinyl pyrrolidone in a mass ratio of 1:0.8-1.
5.
7. A method for preparing a scale inhibitor dispersant for circulating water of a steam turbine, characterized in that: The method comprises the following steps: adding water-soluble zinc salt, stabilizer and corrosion inhibitor into water according to the proportion of the scale inhibitor and dispersant according to any one of claims 1 to 6, stirring to dissolve, and then sequentially adding organic phosphoric acid compound and acrylic acid copolymer, stirring evenly to obtain the product.
Citation Information
Patent Citations
Carboxylic-sulfonic-polyalkylene oxide polymers and their use as scale and corrosion inhibitors
EP0184894A1
Scale inhibitor and scale inhibition method
JP2018009255A
Composition and method for inhibition of metal corrosion
US6447717B1